Bone marrow stromal cell‐derived extracellular matrix promotes osteogenesis of adipose‐derived stem cells. (7th October 2014) - Zhang, Zhiliang; Luo, Xuan; Xu, Haisong; Wang, Lin; Jin, Xin; Chen, Rui; Ren, Xiaoyun; Lu, Yi; Fu, Mingang; Huang, Yixiong; He, Jiyin; Fan, Zhihong
Abstract: Adipose‐derived stem cells (ASCs) can differentiate into multiple cell lineages and favor adipogenesis rather than osteogenesis. Because the extracellular matrix (ECM) component of the stem cell niche is important in stem cell differentiation, we hypothesized that ECM produced by human bone marrow stromal cells (BM‐ECM) could enhance the osteogenic potential of ASCs during in vitro expansion. We have compared the replication and osteogenic differentiation of ASCs expanded on BM‐ECM versus tissue culture plastic (TCP) in vitro and in vivo. During the first two passages, ASC proliferation on BM‐ECM was 3.27‐fold greater than that on TCP. ASCs expanded on BM‐ECM formed more osteogenic colonies and higher expression of osteogenic markers than ASCs expanded on TCP. In nude mice, ASCs that had been expanded on BM‐ECM formed more new bone tissue than those expanded on TCP. The data indicate that BM‐ECM can be used to promote the osteogenic fate of ASCs.